Introduction: Photography, "Race", and Post-Colonial Theory - Hight, Eleanor M.; Sampson, Gary D. (Colonialist Photography, 2002)
The theme of the Annual College Art Association Conference held in Toronto in February 1998 was "The History of Art in a Post-colonial Environment." In response to the call for sessions, we proposed a topic we thought essential to the conference theme: the relationship between photography and Western colonialism. Our hope was to gather a core of papers that would demonstrate, through a variety of subjects and critical methods, how photography functioned as a cultural and political medium intricately tied to the establishment and support of colonialist power. We were particularly concerned with the period from the 1840s to the 1940s, from photography's first experimental "documentary" uses to World War II, after which time many regions under the colonial authority of European nations and the United States struggled for independence. This collection of essays grew out of our CAA session, "Imag(in)ing 'Race' and Place in Colonialist Photography." It includes the expanded session papers of Ayshe Erdogdu, Andrew Evans, Patricia Johnston, and Kim Sichel, as well as additional contributions by Julia Ballerini, Brenda L. Croft, Rebecca DeRoo, John Falconer, Michael Hayes, Oscar E. Vázquez, and the editors. These writers examine a diverse range of photographs produced by Europeans and Americans of peoples and places in Asia, Africa, the Middle East, the Americas, Hawai'i, Oceania, and Australia. Building upon current ideas about the relationship between colonialism and visual representation, the chapters analyze the ways in which photographs operate as complex discursive objects of colonial power and culture.